TRUST as A Pillar of Religious Moderation in Islamic Education - Andi Anugrah Surya Ardhy; Fauziah (Dialogia, 2025)
This study explores the strategic role of Islamic education in promoting religious moderation through a multicultural approach. Responding to the increasing diversity in Indonesian society, the research seeks to answer how Islamic education integrates the values of tolerance, inclusivity, and social harmony into learning. Using a meta-synthesis method, 25 relevant journal articles published between 2020–2024 were analyzed to identify the patterns of implementation, challenges, and strategies in promoting religious moderation. The study finds that religious moderation is practiced through curriculum integration, dialogical pedagogy, and role modeling by educators. A multicultural approach—encompassing inclusive, critical, and humanistic perspectives—enhances empathy and social understanding. However, challenges such as political interference, exclusivist resistance, and pedagogical limitations remain significant. To address these, the study proposes the TRUST model (Tolerance, Respect, Understanding, Solidarity, Togetherness) as a conceptual and practical framework to reinforce harmony in Islamic educational settings. This model bridges Islamic teachings with multicultural values, offering a relevant paradigm for contemporary education. REFERENCES Abdullah, F, and S Herlambang. “Multiculturalism among Students in Madrasah: Knowledge, Challenges, and Social Capital.” Nazhruna: Jurnal Pendidikan Islam 7, no. 2 (2024): 390–408. https://doi.org/10.31538/nzh.v7i2.4710. Abdullah, Munawiah, M. Hasbi Amiruddin, Ernita Dewi, and Nuraini H. A. Mannan. “Moderation of Thought in the Age of Radicalism: The Role of Social Media and Political Education in Countering Hate Content.” Tafkir: Interdisciplinary Journal of Islamic Education 6, no. 1 (January 17, 2025): 94–110. https://doi.org/10.31538/tijie.v6i1.1373. Abidin, Achmad Anwar, and Muhammad Ali Murtadlo. “Curriculum Development of Multicultural-Based Islamic Education as An Effort to Weaver Religious Moderation Values In Indonesia.” The International Journal of Islamic Education, Research and Multiculturalism 2, no. 1 (2020): 29–46. https://doi.org/https://doi.org/10.47006/ijierm.v2i1.30. Afwadzi, B, U Sumbulah, N Ali, and S Z. Qudsy. “Religious Moderation of Islamic University Students in Indonesia: Reception of Religious Texts.” HTS Teologiese Studies / Theological Studies 80, no. 1 (2024). https://doi.org/10.4102/hts.v80i1.9369. Ainissyifa, H, Y M Nasrullah, and N Fatonah. “Empowering Educational Autonomy to Implement Kurikulum Merdeka in Madrasah.” Jurnal Pendidikan Islam 10, no. 1 (2024): 25–40. https://doi.org/10.15575/jpi.v10i1.35133. Alsulami, N D. “Developing Religious Moderation in Indonesian Islamic Schools Through the Implementation of the Values of Islām Wasaṭiyyah.” Jurnal Pendidikan Agama Islam 19, no. 2 (2022): 207–22. https://doi.org/10.14421/jpai.2022.192-03. Aryati, A., and A Suradi. “The Implementation of Religious Tolerance: Study on Pesantren Bali Bina Insani with Bali Hindu Communities.” Jurnal Ilmiah Peuradeun 10, no. 2 (2022): 471–90. https://doi.org/10.26811/peuradeun.v10i2.646. Athoillah, Mohamad, Ahmad Syaeful Rahman, Aep Syaefudin Firdaus, and Muhammad Andi Septiadi. “Policies and Practices Religious Moderation in Pesantren.” Jurnal Pendidikan Islam 10, no. 2 (December 16, 2024): 387–96. https://doi.org/10.15575/jpi.v10i2.27543. Azra, Azyumardi. “Islamic Education and Reintegration of Sciences: Improving Islamic Higher Education.” Media Syari’ah 15, no. 2 (2013): 257–64. http://jurnal.ar-raniry.ac.id/index.php/medsyar/article/view/1779. Burhanuddin, N, and D Ilmi. “Typologies of Religious Moderation in Indonesian Higher Education Institutions.” Journal of Indonesian Islam 16, no. 2 (2022): 455–79. https://doi.org/10.15642/JIIS.2022.16.2.455-479. Chairilsyah, Daviq. “Raising Tolerant Attitude to Children.” Aulad : Journal on Early Childhood 2, no. 3 (December 11, 2019): 81–90. https://doi.org/10.31004/aulad.v2i3.38. Darwanto, A, R C I Prahmana, A Susanti, and I A Khalil. “Transformation of Boarding School Management Models in Enhancing Student Accessibility and Educational Quality.” Jurnal Pendidikan Agama Islam 21, no. 1 (2024): 145–64. https://doi.org/10.14421/jpai.v21i1.8632. Hamid, Noor, and Sri Wahyuni. “A Multicultural Islamic Religious Education Curriculum Development.” Jurnal Pendidikan Islam 14, no. 2 (September 2, 2024): 113–27. https://doi.org/10.38073/jpi.v14i2.1731. Hanafi, Y, M Saefi, T N Diyana, M Alifudin Ikhsan, M T Yani, O A Suciptaningsih, A E Anggraini, and I S Rufiana. “What Content Offers and How Teachers Teach: Religious Moderation-Integrated Teaching in Indonesia.” HTS Teologiese Studies / Theological Studies 79, no. 2 (2023). https://doi.org/10.4102/hts.v79i2.9070. Haryanto, S, and M Muslih. “Uniting Tradition and Modernity: Scientific Paradigms of Pesantren-Based Universities.” Nazhruna: Jurnal Pendidikan Islam 7, no. 3 (2024): 684–704. https://doi.org/10.31538/nzh.v7i3.48. Ichsan, Y, S Syamsudin, and Z Nuryana. “Realizing Islamic Education Based on Religious Moderation with the Wasathiyah Islamic Paradigm from the Perspective of the Qur’an.” Jurnal Pendidikan Agama Islam 21, no. 1 (2024): 247–63. https://doi.org/10.14421/jpai.v21i1.9944. Ismail, Syarof Nursyah, and Zulkarnain Zulkarnain. “Embracing Diversity: Islamic Education through the Multicultural Lens of the Quran.” Edukasia : Jurnal Penelitian Pendidikan Islam 18, no. 2 (December 30, 2023): 203. https://doi.org/10.21043/edukasia.v18i2.25456. Jufri, Darmawati, and St. Wardah Hanafie Das. “The Nature of Multicultural Education in Indonesia: A Perspective on Islamic Education.” Harmony Philosophy: International Journal of Islamic Religious Studies and Sharia 1, no. 4 (December 30, 2024): 01–14. https://doi.org/10.70062/harmonyphilosophy.v1i4.26. Kementerian Agama RI. Moderasi Beragama. Jakarta: Badan Litbang dan Diklat Kementerian Agama RI, 2019. Khasanah, Nur, Achmad Irwan Hamzani, and Havis Aravik. “Religious Moderation in the Islamic Education System in Indonesia.” QALAMUNA: Jurnal Pendidikan, Sosial, Dan Agama 15, no. 1 (2023): 629–42. https://doi.org/10.37680/qalamuna.v15i1.4115. Kosim, M, M Kustati, W R Sirait, S Fajri, S R Febriani, and D D Perrodin. “Developing A Religious Moderation-Based Curriculum Module for Laboratory Madrasah Tsanawiyah in Islamic Higher Education.” Jurnal Pendidikan Islam 10, no. 2 (2024): 350–62. https://doi.org/10.15575/jpi.v10i2.39163. Ma`arif, M A, M H Rofiq, S Kausar, A Sirojuddin, A Kartiko, and M S Hasan. “Shaping Students’ Moderate Islamic Character at Madrasah.” Jurnal Pendidikan Islam 10, no. 2 (2024): 323–35. https://doi.org/10.15575/jpi.v10i2.34029. Mala, Asnal, and Wiwin Luqna Hunaida. “Exploring the Role of Religious Moderation in Islamic Education: A Comprehensive Analysis of Its Unifying Potential and Practical Applications.” Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies) 11, no. 2 (December 31, 2023): 173–96. https://doi.org/10.15642/jpai.2023.11.2.173-196. Mansir, Firman, and Ben Wadham. “Paradigm of H.A.R Tilaar Thinking About Multicultural Education in Islamic Pedagogy and Its Implication in the Era Pandemic Covid-19.” Cendekia: Jurnal Kependidikan Dan Kemasyarakatan 19, no. 2 (December 2, 2021): 253–68. https://doi.org/10.21154/cendekia.v19i2.2612. May, Samantha, Erin K. Wilson, Claudia Baumgart-Ochse, and Faiz Sheikh. “The Religious as Political and the Political as Religious: Globalisation, Post-Secularism and the Shifting Boundaries of the Sacred.” Politics, Religion & Ideology 15, no. 3 (July 3, 2014): 331–46. https://doi.org/10.1080/21567689.2014.948526. Muchtar, Choiriyah, Dwi Noviani, Mardeli, Mutiara, and Manna Dey. “Religious Moderation in The Framework of Life.” International Journal of Islamic Education, Research and Multiculturalism (IJIERM) 4, no. 2 (November 28, 2022): 135–49. https://doi.org/10.47006/ijierm.v4i2.142. Mukarom, Zaenal, Pande Wayan Renawati, Laesti Nurishlah, Djenal Suhara, and Budi Setiawan. “A Multicultural Approach in Islamic Education to Increase Tolerance.” International Education Trend Issues 2, no. 2 (September 8, 2024): 300–307. https://doi.org/10.56442/ieti.v2i2.851. Mulyana, R. “Religious Moderation in Islamic Religious Education Textbook and Implementation in Indonesia.” HTS Teologiese Studies / Theological Studies 79, no. 1 (2023). https://doi.org/10.4102/HTS.V79I1.8592. Musyahid, Musyahid, and Nur Kolis. “Religious Moderation Implementation in Islamic Education: A Systematic Review.” FITRAH: Jurnal Kajian Ilmu-Ilmu Keislaman 9, no. 2 (December 31, 2023): 265–84. https://doi.org/10.24952/fitrah.v9i2.9547. Muthoifin, Muthoifin, Mariam Elbanna, Aboubacar Barry, Ishmah Afiyah, Andri Nirwana, Bernardlauwers Bernardlauwers, and Rezaul Islam. “Islamic Education Management in Promoting Multiculturalism, Democracy and Harmony.” Journal of Management World 2025, no. 1 (January 13, 2025): 445–56. https://doi.org/10.53935/jomw.v2024i4.713. Naim, N, A Aziz, and T Teguh. “Integration of Madrasah Diniyah Learning Systems for Strengthening Religious Moderation in Indonesian Universities.” International Journal of Evaluation and Research in Education 11, no. 1 (2022): 108–19. https://doi.org/10.11591/ijere.v11i1.22210. Nasir, M, and M.K. Rijal. “Keeping the Middle Path: Mainstreaming Religious Moderation through Islamic Higher Education Institutions in Indonesia.” Indonesian Journal of Islam and Muslim Societies 11, no. 2 (2021): 213–41. https://doi.org/10.18326/ijims.v11i2.213-241. Nasution, S, H Asari, and H Al-Rasyid. “Kitab Kuning and Religious Moderation: A Study on State Islamic Universities in Indonesia.” Journal of Al-Tamaddun 19, no. 2 (2024): 73–88. https://doi.org/10.22452/JAT.vol19no2.5. Nuha, U, Z. Arifin, Y Kuswandari, and A R A Razak. “Religion Teachers’ Strategies to Internalize Tolerance Values at Catholic and Islamic Schools in Bajawa, Nusa Tenggara Timur.” Jurnal Pendidikan Agama Islam 18, no. 2 (2021): 295–306. https://doi.org/10.14421/jpai.2021.182-05. Nurlaelah, Nurlaelah, Jamali Jamali, Didin Nurul Rosidin, and Siti Fatimah. “A Multicultural Approach to Islamic Religious Education.” International Journal of Social Science and Human Research 06, no. 04 (April 18, 2023). https://doi.org/10.47191/ijsshr/v6-i4-38. Nurrohim, Ahmad, Angga Hernanda Setiawan, Andri Arungga Sweta, and Muthoifn. “The Concept of Islamic Moderation in Indonesia: A Comparative Study in Tafsir An-Nur and Tafsir of the Ministry of Religious Affairs (MORA).” International Journal of Religion 5, no. 10 (June 24, 2024): 2110–25. https://doi.org/10.61707/5b1e9h02. Nyanasuryanadi, Partono, Muqarranah Sulaiman Kurdi, Musyarrafah Sulaiman Kurdi, Pandu Adi Cakranegara, Dendi Pratama, and Nilawati Nilawati. “Mainstreaming the Value of Religious Moderation by Teachers in the Digital Era.” AL-ISHLAH: Jurnal Pendidikan 15, no. 2 (April 12, 2023): 1357–68. https://doi.org/10.35445/alishlah.v15i2.3198. “PPIM Gelar FGD Tentang Moderasi Beragama Di Kalangan Guru PAI.” Accessed February 19, 2025. https://uinjkt.ac.id/index.php/id/ppim-gelar-fgd-tentang-moderasi-beragama-di-kalangan-guru-pai. Prayitno, H.J., S Hidayat, M Ali, and F Sugiarto. “Character Strengthening Model of Religious Moderation Praxis Method to Improve and Develop Student Morale.” Revista de Gestao Social e Ambiental 18, no. 2 (2024). https://doi.org/10.24857/RGSA.V18N2-076. Rahmadi and Hamdan. “Religious Moderation in The Context of Islamic Education : A Multidisciplinary Perspective and Its Application in Islamic.” Khazanah: Jurnal Studi Islam Dan Humaniora 21, no. 1 (2023): 59–82. https://doi.org/10.18592/khazanah.v20i1.8487. Rahman, B A. “Islamic Revival and Cultural Diversity: Pesantren’s Configuration in Contemporary Aceh, Indonesia.” Indonesian Journal of Islam and Muslim Societies 12, no. 1 (2022): 201–29. https://doi.org/10.18326/ijims.v12i1.201-229. Riyawi, Mohd. Rafi, and Denny Febriansyah. “The Urgency of Religious Moderation in the Perspective of Islamic Education.” Journal of Social Research 2, no. 8 (July 24, 2023): 2578–91. https://doi.org/10.55324/josr.v2i8.1309. Saepudin, A, T Supriyadi, D Surana, and I Asikin. “Strengthening Character Education: An Action Research in Forming Religious Moderation in Islamic Education.” International Journal of Learning, Teaching and Educational Research 22, no. 12 (2023): 84–105. https://doi.org/10.26803/ijlter.22.12.5. Sidik, M F, V P Vachruddin, E F Rusydiyah, A S Pertiwi, and M A Darmawan. “Conceptualization of the Integrated Islamic Religious Education Curriculum: A Literature Study at Imam Hatip Schools, Turkey and MAN Insan Cendekia Indonesia.” Jurnal Pendidikan Agama Islam 21, no. 1 (2024): 111–30. https://doi.org/10.14421/jpai.v21i1.7617. Sule, Muhammad Maga, and Attahir Shehu Mainiyo. “Effectiveness of Social Media Platforms in Disseminating Qur’anic Teachings Among Contemporary Muslims.” Spektra: Jurnal Ilmu-Ilmu Sosial 5, no. 1 (September 22, 2023): 47–64. https://doi.org/10.34005/spektra.v5i1.2668. Sumadiyah, Siti, and Sri Wahyuni. “Development of Multicultural Islamic Religious Education Curriculum in Building Religious Moderation at Universitas Islam Kadiri Kediri.” EDU-RELIGIA : Jurnal Keagamaan Dan Pembelajarannya 7, no. 1 (June 26, 2024): 80–89. https://doi.org/10.52166/edu-religia.v7i1.6919. Suparta. “Religious Moderation-Based Curriculum for Urban Muslims : A Study in the Islamic University of Indonesia Islamic Boarding School.” AKADEMIKA: Jurnal Pemikiran Islam 29, no. 1 (2024). https://doi.org/10.32332/akademika.v29i1.8732. Thoyib, M E, A Degaf, A A Fatah, and M Huda. “Religious Tolerance among Indonesian Islamic University Students: The Pesantren Connection.” Journal of Al-Tamaddun 19, no. 2 (2024): 239–50. https://doi.org/10.22452/JAT.vol19no2.16. Turhamun. “Implementation of Religious Moderation in Non-Formal Education in Forming a Multicultural Society.” International Journal of Social Science and Religion (IJSSR), January 3, 2024, 1–22. https://doi.org/10.53639/ijssr.v5i1.196. Wardi, M, M U Fithriyyah, Z Fathorrahman, and T Hidayat. “Implementation of Religious Moderation Values Through Strengthening Diversity Tolerance in Madrasah.” Jurnal Pendidikan Islam 9, no. 2 (2023): 241–54. https://doi.org/10.15575/jpi.v9i2.27952.